Pancasila and Justice for Shared Land: Sustainable Communal Governance in Indonesia’s Forest Areas - Muslim Lobubun; Iryana Anwar; Ahmed Mohamed Barak (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2026)
Land reform in Indonesia’s forest regions still struggles with long-standing, deep-rooted barriers. Three problems stand out: the strong state-control approach, fragmented institutions, and the insufficient recognition of Indigenous peoples’ rights in practice. Together, these issues highlight a gap between Indonesia’s constitutional promise of Pancasila-based social justice and the way forest land policies are largely handled through administrative, rule-following mechanisms. This study explores how the values of Pancasila social justice and sustainable development can be reflected in the legal framework for agrarian reform in forest areas. It reviews shortcomings in current policies, including how the Land Reform Object (TORA) program is implemented and how Presidential Regulation No. 62 of 2023 is applied. Based on this analysis, the study proposes a Sustainable Communal Land Governance paradigm as an alternative direction for reform. Using a normative–critical legal method, the research examines laws and regulations, court decisions, and relevant academic scholarship. The findings show that existing agrarian reform efforts remain too centered on the state, limiting both substantive justice for affected communities and ecological sustainability for forest ecosystems. The study concludes that the Sustainable Communal Land Governance paradigm can provide a practical and stronger basis for agrarian legal reform—by combining Pancasila social justice, recognition of communal land rights, and sustainability principles, while reshaping the state’s role into a facilitator and protector of ecological balance.